Working capital management, company performance, and funding barriers on Indonesian Firms - Liza Handoko; Chessia Violeta (Universitas Sebelas Maret, 2020)
The purpose of this study is to examine the relationship between investment in working capital measured by trade credit and corporate performance in 463 companies in Indonesia between 2007 and 2017. This research confirms the non-linearity inverted U shape of the link between working capital and corporate performance. It suggests that there is an optimal point of investment that is beneficial for the company. This research also examines the impact of financial constraint and investment level on working capital. Our finding shows that companies that experience financial constraints have lower investment levels than those without financial constraints.